Internalization of Character Values in Learning Process Using MSHR Model - Sudrajat, Hendar; Syaflita, Dina (Proceedings of the UR International Conference on Educational Sciences, 2018)
Education is an effort to build character of students through fostering Affective domains to form Good Feeling, Cognitive domain to form Good Knowing, and Psychomotor domain to form Good Acting. Unfortunately, in affective domain learning activities or attitudes tend to be ignored for various reasons. This gives an overview of the lack of awareness of educators to pay attention to the affective aspects of learning. For that, it is necessary to habituate the internalization of character values by educators through a simple strategy, namely MSHR (Motivation, Socialization, Habituation, and Remediation). The goals of this strategy is to help teacher internalize character values in learning activities simplely. This type of research is R & D research using the Plomp development model. Validity and practicality tests carried out by experts and practitioners through oral assessment using questionnaire instruments. The effectiveness test is done by asking the studentâs opinions on learning activities using the MSHR attitude learning model. The internalization can be carried out in the learning time section of the study, at the beginning, mid, or end of activities. The results of the study illustrate that the MSHR model is valid, practical, and effective to be used in learning activities.